146k views
1 vote
Can anyone help me solve this step by step!
Thanks!!

Can anyone help me solve this step by step! Thanks!!-example-1
User TasseKATT
by
6.1k points

1 Answer

2 votes

You have a system of equations in two unknowns, x and y.

2x - 3y = -1

y = x - 1

There are several methods for solving systems of equations, but since your second equation is already solved for y, I will use the substitution method since in that method, the first step is to solve an equation for one variable.

The second equation tells us that y is the same as x - 1.

Where you see y in the first equation, substitute it with x - 1.

Here is the first equation with the y in bold face.

2x - 3y = -1

Now we do the substitution step.

We rewrite the first equation, but we write x - 1 instead of y. We are substituting x - 1 for y.

2x - 3(x - 1) = -1

As you can see, y was substituted by x - 1. The parentheses are needed to show we need to multiply 3 by x - 1 and not just be x.

Now we have a single equation is a single unknown, so we can solve for x.

2x - 3(x - 1) = -1

Distribute the -3.

2x - 3x + 3 = -1

Add like terms on the left side.

-x + 3 = -1

Subtract 3 from both sides.

-x = -4

Divide both sides by -1.

x = 4

Now that we know x, we substitute x into either of the original equations to find y. Since the second original equation is already solved for y, I will use the second original equation.

y = x - 1

y = 4 - 1

y = 3

Solution: x = 4 and y = 3


User Captray
by
5.9k points